Validity and Reliability: An Ability Assessment Instrument to Identify the Number Concept - Bella Vira Rista; Agung Gede Agung; Putu Rahayu Ujianti (Indonesian Journal Of Educational Research and Review, 2020)
This study aims to develop an instrument of assessment of the ability to recognize the concept of the number for the children in Kindergarten. This research is development research by applying RDR model research (Research, Development, Research). The subjects in this study were students of group A kindergarten in Buleleng Regency. Variables studied are instruments of introduction to the concept of numbers that become the necessary foundation in mathematics learning. Data collection is done using questionnaires and interviews. The data obtained is analyzed with the help of Microsoft Excel 2010. The results of this study state that the validity and reliability of the instrument are categorized very well. The effects on the validity test are indicated with a score of 0.91. As for the results of the reliability, the test gets a score of 0.81. This research is expected to be used as a reference in the learning assessment process for the children in Kindergarten in knowing the concept of numbers.